El impacto de la gamificación en el aprendizaje de matemáticas en estudiantes de secundaria en la Unidad Educativa "Nicolás Maquiavelo", año lectivo 2024-2025. - Gaona Ávila, Carmen Cecilia (2025)
The present research is based on the impact of gamification in the learning of Mathematics in high school students in the Educational Unit “Nicolás Maquiavelo”; where its purposes consist of examining the way in which gamification affects their performance, measuring the degrees of stimulation of the students. Where the methodological approach is quantitative, where its technique is the survey. Where it was obtained that of the 100% of teachers represented in 11, 7 representing 64% said that they totally agree that gamified activities would increase the interest of students in learning Mathematics, while 27% that is given of 3 respondents said that they agree, in disagreement said 1 which is 9%. In the same way 6 respondents representing 55% said that they consider that students would be very engaged in learning Mathematics, by using games and gamified activities. Referring to students say that 3% out of a total of 77, said that in all classes they perceive that the teacher frequently uses gamification techniques; while 6% defined from 5 respondents said sometimes; while 26%, coming from 20 said rarely; and never indicated in 65% which is given out of 50 responses given from students. Thus, the findings indicate the need for teacher training to integrate gamification into their teaching techniques, in accordance with students' expectations and tastes.